School-based interventions to prevent anxiety and depression in children and adolescents in low- and middle-income countries: A systematic review - Sharone Zhameden Dieu Yin; Mei Ken Low; Masuma Pervin Mishu (PLoS ONE, 2025)
Background Anxiety and depression are on the rise among children and adolescents globally. Low- and middle-income countries (LMICs) face heightened vulnerability due to limited resources, restricted access to mental health services, socioeconomic disparities and widespread mental health stigma. Schools offer a unique and potentially impactful setting for preventive interventions targeting anxiety and depression in young individuals. Aim We aimed to identify empirical research to explore the effectiveness of school-based interventions designed to prevent anxiety and depression among children and adolescents in LMICs. Method Ovid MEDLINE, Embase, PsycINFO and CENTRAL were systematically searched for articles published between 2018 and July 2023. Randomised controlled trials that evaluated school-based interventions for children and adolescents aged 4–18 years in LMICs were included. Only studies in English language were included. The primary outcomes were anxiety and/or depressive symptoms. Risk-of-bias assessments were performed. Results Out of 3863 articles identified, six studies comprising 1587 students met the inclusion criteria. Among the four studies that examined interventions for the prevention of both anxiety and depression, as well as anxiety alone, only one study showed a reduction in anxiety symptoms. In the case of depression, three out of four studies reported improvements in depressive symptoms. The finding suggests a potential effectiveness of preventive interventions against depression, but not anxiety. However, this finding should be interpreted with caution given the limited number of studies identified. All studies were either classified as high risk of bias or having some concerns. Conclusion There is some evidence of the effectiveness of school-based interventions in preventing anxiety and depression among young people in LMICs. Further research is necessary to gain a more comprehensive understanding of this critical issue. Moving forward, it is crucial to enhance and broaden existing school-based prevention programs in these nations, exploring different intervention strategies tailored to their specific contextual factors.